Metabolic dysfunction-associated steatotic liver disease-induced changes in the antioxidant system: a review - Svobodová, Gabriela; Horní, Martin; Velecká, Eva; Boušová, Iva (Archives of toxicology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a heterogeneous condition characterized by liver steatosis, inflammation, consequent fibrosis, and cirrhosis. Chronic impairment of lipid metabolism is closely related to oxidative stress, leading to cellular lipotoxicity, mitochondrial dysfunction, and endoplasmic reticulum stress. The detrimental effect of oxidative stress is usually accompanied by changes in antioxidant defense mechanisms, with the alterations in antioxidant enzymes expression/activities during MASLD development and progression reported in many clinical and experimental studies. This review will provide a comprehensive overview of the present research on MASLD-induced changes in the catalytic activity and expression of the main antioxidant enzymes (superoxide dismutases, catalase, glutathione peroxidases, glutathione S-transferases, glutathione reductase, NAD(P)H:quinone oxidoreductase) and in the level of non-enzymatic antioxidant glutathione. Furthermore, an overview of the therapeutic effects of vitamin E on antioxidant enzymes during the progression of MASLD will be presented. Generally, at the beginning of MASLD development, the expression/activity of antioxidant enzymes usually increases to protect organisms against the increased production of reactive oxygen species. However, in advanced stage of MASLD, the expression/activity of several antioxidants generally decreases due to damage to hepatic and extrahepatic cells, which further exacerbates the damage. Although the results obtained in patients, in various experimental animal or cell models have been inconsistent, taken together the importance of antioxidant enzymes in MASLD development and progression has been clearly shown.
Keywords: oxidační stres; antioxidancia; reaktivní formy kyslíku; Catalytic activity; Metabolic dysfunction-associated steatotic liver disease; Expression; Reactive Oxygen Species; Animals; lidé; játra; Antioxidants; Humans; zvířata; Antioxidant enzyme; Glutathione; ztučnělá játra; Liver; Oxidative Stress; Fatty Liver